Burn pit exposure in military personnel and the potential resulting lung and neurological pathologies - Penuelas, Veronica L.; Lo, David D. (Frontiers in Environmental Health, 2024)
Introduction: Military personnel and local civilians at various deployment locations are plagued with serious health conditions. Evidence points to burn pit emissions as the cause of these pathologies; however, similar diseases are also caused by environmental exposures, smoking, genetic predispositions, or other comorbidities. Burn pits, which are large smoldering piles of refuse ignited with jet or diesel fuel, contain human and medical waste as well as paint, plastics, ammunition, and other materials -each of which can be attributed to health concerns in other industrial settings. Here we compare various pathologies attributable to toxic aerosol exposures and discuss distinct pathologies that may be linked to burn pit exposures.We performed a literature review where we provide information on toxic exposures that may pose relevance to burn pit exposure and furthermore, highlight what is already known about burn pit exposures and what steps need to be taken to diagnose and correlate certain respiratory pathologies to chronic exposure from overseas burn pits.We conducted searches through PubMed and Google Scholar to determine where gaps in our knowledge of burn pit exposure lie. Thorough review on jet-fuel properties and particulate matter were performed as supporting evidence of potential toxins from burn pit emissions.To date, studies on burn pit emissions consist mainly of systematic reviews and discussions to address the problem, with very few acute-exposure studies and little to no chronic-exposure studies. We found that symptoms range from respiratory pathologies to neurological deficits, but treatment has been limited as medical facilities, such as the Veterans Administration (VA), require proof that a condition is service-connected.To determine the effects of burn pit exposure on humans, chronic exposure to mimicked burn pit emissions is necessary to draw definitive conclusions between phenotypic differences in pathologies linked to exposure. By determining phenotypic differences, conclusions can be made about the pathologic origins, potentially leading to future diagnoses and treatments for veterans and affected civilians.